2012
DOI: 10.1007/s12630-012-9734-4
|View full text |Cite
|
Sign up to set email alerts
|

Prehabilitation to enhance postoperative recovery for an octogenarian following robotic-assisted hysterectomy with endometrial cancer

Abstract: This report provides suggestive evidence that a prehabilitation program optimized the health of this elderly patient and may have prevented a further episode of postoperative delirium. Prehabilitation protocols should be evaluated in clinical trials to evaluate their efficacy and the target populations who may benefit and to elucidate the underlying mechanisms responsible for enhanced recovery in the perioperative setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 20 publications
1
49
0
Order By: Relevance
“…Other studies have found that exercise in the prehabilitation period was feasible for sedentary individuals [39]. The results from a single-case report hinted that prehabilitation may be beneficial for elderly patients [40] which, in turn, supported the findings by Lai et al [17].…”
Section: Discussionsupporting
confidence: 69%
“…Other studies have found that exercise in the prehabilitation period was feasible for sedentary individuals [39]. The results from a single-case report hinted that prehabilitation may be beneficial for elderly patients [40] which, in turn, supported the findings by Lai et al [17].…”
Section: Discussionsupporting
confidence: 69%
“…We therefore recommend the assessment of prehabilitation programmes, comprising the optimisation of patients prior to surgical treatment, to improve modifiable risk factors. Although implementation remains a challenge because of a restricted time period between diagnosis and treatment, previous studies have shown promising results [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…It identifies potentially modifiable interventions to maximize independence, social support, cognition, and quality of life while reducing risks for poor outcomes such as delirium, worsening disability, post-operative complications, rehospitalization, or surgical mortality. 20, 21 The CGA identifies not only physical frailty but a wide variety of vulnerabilities. The CGA predicts post-surgical and overall mortality among patients with cancer, 9, 22, 23 and a pre-operative geriatric assessment improves surgical outcomes in patients with cancer.…”
Section: Importance Of the Frailty Syndrome Assessment To Cancer Carementioning
confidence: 99%